Computer science : the hardware, software and heart of it - Aho, Alfred V.; Blum, E. K. [ (Edward K.)] , 1923- (Springer, 2011)
This volume focuses on the deeper aspects of software and hardware -- the two recognized subdivisions that make up the field of computer science. The text offers classical theoretical computer science concepts such as Unsolvability and Undecidability, among other key topics